SpaceOAR© hydrogel rectal dose reduction prediction model: a decision support tool. Issue 6 (30th April 2020) - Paetkau, Owen; Gagne, Isabelle M.; Alexander, Abraham
Abstract: Prostate cancer external beam radiation therapy can result in toxicity due to organ at risk (OAR) dose, potentially impairing quality of life. A polyethylene glycol‐based spacer, SpaceOAR© hydrogel (SOH), implanted between prostate gland and rectum may significantly reduce dose received by the rectum and hence risk of rectal toxicity. SOH implant is not equally effective in all patients. Determining patients in which the implant will offer most benefit, in terms of rectal dose reduction, allows for effective management of SOH resources. Several factors have been shown to be correlated with reduction in rectal dose including distance between rectum and planning treatment volume (PTV), volume of rectum in the PTV, and change in rectum volume pre‐ to post‐SOH. Several of these factors along with other pre‐SOH CT metrics were able to predict reduction in rectal dose associated with SOH implant. Rectal V55Gy metric, was selected as the dose level of interest in the context of 60 Gy in 20 fraction treatment plans. Models were produced to predict change in RV55Gy and pre‐SOH hydrogel RV55Gy. These models offered R‐squared between 0.81 and 0.88 with statistical significance in each model. Applying an ω 1  = 3% lower limit of pre‐SOH RV55 Gy and an ω 2  = 3.5% lower limit on change in RV55 Gy, retained 60% of patients experiencing the largest rectal dose reduction from the hydrogel. This may offer a clinically useful tool in deciding which patients should receive SOH implant given limited resources. Predictive models, nomograms, and a workflow diagram were produced for clinical management of SOH implant.